TRENDS IN INNOVATIVE MANAGEMENT DECISIONS: THE ROLE OF MEDIA LITERACY IN OVERCOMING THE CHALLENGES OF THE PANDEMIC - ZRYBNIEVA, IRYNA; Zavolichna, Tetyana (Deutscher Wissenschaftsherold • German Science Herald, 2021)
The article examines the issue of identifying new trends in the management decision-making system in the face of the COVID-19 pandemic. Groups of new risks at the level of national economy and business in the context of management theories "overcoming the resistance to change" are systematized. It is generalized that the process of making managerial decisions in a pandemic can be called a mental process with a significant emotional load. The effectiveness of decisions depends largely on the skills of the manager to solve non-standard tasks and problems. The importance of the development of media literacy as a factor of adaptation to the challenges of the pandemic - as a tool to overcome the panic of the population and as a factor of managerial innovation in the transition to telecommuting. 8 new trends in management decisions in the current challenges of the pandemic are substantiated. It is established that the media competence of managers allows to determine the right goal at the beginning of the problem and to model ways to avoid it. This will predict development trends and establish the mode of operation of the firm, taking into account any factors in the development of pandemic waves.
Keywords: managerial decisions; media literacy; innovative trends; pandemic challenges; resistance to change; teleworking